OPPORTUNITIES FOR LOW INVESTMENT RECYCLING WASTE TIRE DERIVED MATERIALS INTO RUBBER PAVERS - Ciprian Bulei; Mihai–Paul Todor; Imre Kiss (Applied Engineering Letters, 2017)
Over the years, recycling waste tires into civil engineering applications, especially into asphalt paving mixtures and Portland cement concrete, has been gaining more and more interests. In this study, the use of crumb rubber to replace coarse and fine aggregates in concrete pedestrian block was studied. This review summarizes the recent advances in the use of waste tire rubber into civil engineering. The main objective of this study was to investigate the potential utilization of rubber waste in concrete matrix, as fine aggregates, to develop lightweight construction materials such a rubber paver. Due to the increasingly serious environmental problems presented by waste tires, the feasibility of using elastic and flexible tire–rubber particles as aggregate in concrete is investigated in this study. Tire–rubber particles composed of tire chips, crumb rubber, and a combination of tire chips and crumb rubber, were used to replace mineral aggregates in concrete.